2019
DOI: 10.1080/02640414.2019.1568173
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sodium bicarbonate ingestion on cycling performance and acid base balance recovery in acute normobaric hypoxia

Abstract: The effects of sodium bicarbonate ingestion on cycling performance and acid base balance recovery in acute normobaric hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 42 publications
8
45
2
3
Order By: Relevance
“…However, despite an apparent influence of the dietary intervention on acid-base balance parameters and blood buffer capacity, the alkalizing or acidizing diets had no significant effect on PTSR-related performance parameters (PF, MF, and FI), or on the associated physiologic responses of La max and HR. It was previously reported that pre-alkalization prior to exercise had an ergogenic effect for anaerobic exercise performance under normoxic [32,40,42] and hypoxic conditions [32,[35][36][37][43][44][45]. However, whereas NaHCO 3 ingestion is a well-established method for an enhancement of anaerobic performance, the influence of an alkalizing diet on anaerobic exercise performance is still controversially discussed [67] and some investigations reported for less pronounced systemic alkalinity, blood buffer capacity, and an unaffected anaerobic exercise performance after an alkalizing diet [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, despite an apparent influence of the dietary intervention on acid-base balance parameters and blood buffer capacity, the alkalizing or acidizing diets had no significant effect on PTSR-related performance parameters (PF, MF, and FI), or on the associated physiologic responses of La max and HR. It was previously reported that pre-alkalization prior to exercise had an ergogenic effect for anaerobic exercise performance under normoxic [32,40,42] and hypoxic conditions [32,[35][36][37][43][44][45]. However, whereas NaHCO 3 ingestion is a well-established method for an enhancement of anaerobic performance, the influence of an alkalizing diet on anaerobic exercise performance is still controversially discussed [67] and some investigations reported for less pronounced systemic alkalinity, blood buffer capacity, and an unaffected anaerobic exercise performance after an alkalizing diet [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, power output for tests with continuous or repeated high-intensity exercise longer than 45 s, like the 3-min all-out critical power test and repeated sprints, is often reduced in acute hypoxia [20][21][22]24,32]. Therefore, we propose that performance tests assessing for anaerobic, high-intensity exercise performance in hypoxic conditions should last for more than 45 s. A number of studies have also examined the positive effects of supplementation with ergogenic aids such as sodium bicarbonate (NaHCO 3 ) or dietary nitrate as alkalotic buffers for attenuation of the impaired exercise performance under hypoxic conditions [32,[35][36][37][38][39]. Ingestion of NaHCO 3 increases the [HCO 3 − ] concentration in extracellular fluids, which leads to an enhanced buffering of hydrogen ([H + ])…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations